PENGARUH RELEVANSI NILAI TERHADAP KEPUTUSAN INVESTOR - BIMO SETYA PERMANA, ARYO (Jurnal Akuntansi AKUNESA, 2015)
Financial statements that had been published must have one of qualitative characteristics which is value relevance. According to APB Statement No. 4, relevant accounting information must contain an informative and clear information suitable for its user spesifications, like investor, for making different decisions. An investor was proxied by stock price changes and stock return. This study aims to examine whether there is any influence of relevant accounting informations in financial statements toward stock price changes and stock returns. Accounting informations that have been used were book value per share (BVPS) and earning per share (EPS), because those informations are closely related to investors. The result showed that the relevant accounting informations which were measured by BVPS and EPS, were not influencing toward stock price changes. However, stock returns, were influenced. Thus, investors today may not consider the BVPS and EPS on stock price, but they are still considering BVPS and EPS on stock return as basis of investment desicion. Keywords: Value relevance, accounting information, stock price changes, stock returns, BVPS, EPS